Variations in orthodontic bracket retention related to base design. Comparison of foil mesh and anchor pylons brackets - Gibas-Stanek, Marta; Williams, Stephen; Ryniewicz, Wojciech I.; W. Loster, Bartłomiej (Journal of Stomatology, 2017)
of metal brackets with foil mesh (3M, Victory Series), one piece metal brackets (Cannon Ultra) and aesthetic plastic brackets (Cannon Ultra) and to evaluate the sandblasting effect on previously used metal bracket bases regarding their bonding ability. Materials and Methods.A total of seventy human third molars were divided into four groups, and brackets were bonded to the enamel using Transbond XT. After 24 hours of storage, brackets were debonded with Instron Universal Testing Machine® and shear bond strength was recorded. Metal brackets were sandblasted until all visible bonding material was removed from the bracket base and then the bonding procedure and shear bond testing were repeated. Shapiro-Wilk test was used to check normal distribution. Student’s t-test was used to compare the shear bond strength. Results. The shear bond strength of one-piece metal brackets is significantly bigger (18.93MPa) than metal brackets with foil mesh (12.53MPa). Metal brackets in general demonstrate better bonding properties than aesthetic plastic brackets (8.61MPa). There is no statistically significant difference in shear bond strength between new and re-used sandblasted brackets. Conclusions. One-piece brackets with anchor pylons demonstrate better bonding properties but there is a higher risk of enamel damage during debonding of re-used sandblasted brackets.